Association Between Specific Childhood Adversities and Symptom Dimensions in People With Psychosis: Systematic Review and Meta-Analysis. (9th April 2021) - Alameda, Luis; Christy, Angeline; Rodriguez, Victoria; Salazar de Pablo, Gonzalo; Thrush, Madeleine; Shen, Yi; Alameda, Beatriz; Spinazzola, Edoardo; Iacoponi, Eduardo; Trotta, Giulia; Carr, Ewan; Ruiz Veguilla, Miguel; et al.
Abstract: Despite the accepted link between childhood abuse and positive psychotic symptoms, findings between other adversities, such as neglect, and the remaining dimensions in people with psychosis have been inconsistent, with evidence not yet reviewed quantitatively. The aim of this study was to systematically examine quantitatively the association between broadly defined childhood adversity (CA), abuse (sexual/physical/emotional), and neglect (physical/emotional) subtypes, with positive, negative, depressive, manic, and disorganized dimensions in those with psychosis. A search was conducted across EMBASE, MEDLINE, PsychINFO, and Cochrane Libraries using search terms related to psychosis population, CA, and psychopathological dimensions. After reviewing for relevance, data were extracted, synthesized, and meta-analyzed. Forty-seven papers were identified, including 7379 cases across 40 studies examining positive, 37 negative, 20 depressive, 9 disorganized, and 13 manic dimensions. After adjustment for publication bias, general adversity was positively associated with all dimensions (ranging from r = 0.08 to r = 0.24). Most forms of abuse were associated with depressive (ranging from r = 0.16 to r = 0.32), positive (ranging from r = 0.14 to r = 0.16), manic ( r = 0.13), and negative dimensions (ranging from r = 0.05 to r = 0.09), while neglect was only associated with negative ( r = 0.13) and depressive dimensions (ranging from r = 0.16 to r = 0.20). When heterogeneity was found, it tended to be explained by one specific study. The depressive dimension was influenced by percentage of women (ranging from r = 0.83 to r = 1.36) and poor-quality scores (ranging from r = −0.21 and r = −0.059). Quality was judged as fair overall. Broadly defined adversity and forms of abuse increase transdimensional severity. Being exposed to neglect during childhood seems to be exclusively related to negative and depressive dimensions suggesting specific effects.